ANALYSIS CURIOSITY AND ANALOGY ABILITIES OF COLLEGE STUDENT REVIEWED FROM A SCIENTIFIC APPROACH AT THE UNIVERSITY OF MUHAMMADIYAH BONE - A. St. Aisyah Nur; Anwar Ramli; Mrs. Inanna; Andi Muhamad Iqbal Akbar Asfar; A. M. Irfan Taufan Asfar; Mrs. Ernawati (JIRA: Jurnal Inovasi dan Riset Akademik, 2021)
Curiosity is an attitude and action that always tries to find out more deeply and broadly from something that is learned. Meanwhile, analogy is a thought process to draw conclusions based on similar processes or data. This is inversely proportional to the reality in the field based on the observations of researchers at University of Muhammadiyah Bone, researchers see that the curiosity and analogy skills of college student in the economic learning process are still classified as very low. Lecturers can strive for learning by using innovative, effective and creative learning, which can provide opportunities and encourage college student to have high curiosity in order to practice their analogical reasoning skills. In connection with this, the efforts made by researchers to build curiosity and analogy skills of college student in economic learning, namely the need for a scientific approach or a scientific process-based approach which is the organization of learning experiences in a logical order including the learning process by observing, questioning, collecting information, reason (associate) and communicate. The type of research used is quantitative research using experimental quantitative methods. The research design used, namely Quasi Experimental Design with the form of Non-equivalent Control Group Design. The results of this study are proven by the results of the analysis of the recapitulation of the student's analogy ability test which can be seen in the average final test in the experimental class, which is 7,621 and the initial test reaches a value of 6,961. While the results of the final test recapitulation of the analogy ability of college student in the control class reached a value of 6,276 while the initial test results reached a value of 7.5. While the results of student responses are in the valid and reliable category.